Makna dalam Malak Lael No’o pada Masyarakat Sonbai di Desa Bijeli: Sebuah Kajian Semiotika - Tuan, Herson Arif Agendis; Liubana, Metropoly M.J.; Oki, Maria Prisila (Jubindo: Jurnal Ilmu Pendidikan Bahasa dan Sastra Indonesia, 2019)
Problem found in this research is about kind of meaning in Malak used by Sonbai society in Bijell village, Noemuti sub-district, Timor Tengah Utara regency. The aim of this research is to find out and describe meanings in malak lael lo’o used by Sonbai society that was analyzed by using semiotic theory of Roland Barthes. The method used in this research is qualitative descriptive to describe and analyze meaning in malak lael lo’o used by Sonbai society. Based on data analysis, it was found that there are three signs that shape malak lael lo’o, they are lael lo’o (taro’ leaf), klus (cross), and pen-pene (flag).